Islamic Education Teachers’ Perceptions of the Implementation of the Merdeka Curriculum in Building the Religious Character of State Madrasah Ibtidaiyah Students in Binjai City - Zailani; Azmaliah; Rahmah, Nur (EDUTEC : Journal of Education And Technology, 2025)
This study aims to analyze the perceptions of Islamic Religious Education (IRE) teachers toward the implementation of the Merdeka Curriculum at Madrasah Ibtidaiyah Negeri (MIN) Kota Binjai and its contribution to strengthening students’ religious character. This research employed a qualitative descriptive approach through interviews, observations, and documentation. The study involved five informants, consisting of the principal and four IRE teachers. The findings reveal that Islamic Religious Education teachers at MIN Kota Binjai have a positive perception of the implementation of the Merdeka Curriculum, viewing it as an effort aligned with strengthening students’ religious character and adapting education to contemporary needs. Although they face challenges such as limited learning facilities and insufficient technical training, the teachers demonstrate strong commitment through participation in MGMP (Subject Teacher Forum), internal training, and collaborative module development. The implementation of the Merdeka Curriculum has significantly contributed to shaping students’ religious character through Profil Pelajar Pancasila (P5) projects, worship activities, and reflective learning that instills values of honesty, discipline, and tolerance. Optimization efforts are carried out through technology-based learning innovations, integration of Islamic values across subjects, and the creation of a religious learning environment. Overall, it can be concluded that the Merdeka Curriculum has been effectively utilized as an essential instrument in developing a generation that is intellectually, spiritually, and morally excellent.